2022
DOI: 10.1038/s43705-022-00130-7
|View full text |Cite
|
Sign up to set email alerts
|

The plant rhizosheath–root niche is an edaphic “mini-oasis” in hyperarid deserts with enhanced microbial competition

Abstract: Plants have evolved unique morphological and developmental adaptations to cope with the abiotic stresses imposed by (hyper)arid environments. Such adaptations include the formation of rhizosheath–root system in which mutualistic plant–soil microbiome associations are established: the plant provides a nutrient-rich and shielded environment to microorganisms, which in return improve plant-fitness through plant growth promoting services. We hypothesized that the rhizosheath–root systems represent refuge niches an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 104 publications
(114 reference statements)
1
14
0
Order By: Relevance
“…Driven by the substantial overlap in the structures of newly discovered antimicrobial compounds from Streptomyces , researchers have begun to focus on rare actinobacteria, which are viewed as vast potential reservoirs of novel natural products ( Dhakal et al, 2017 ). Some of the rare actinobacteria detected in this study, such as members of Actinokineospora , Micromonospora , and Nocardia , inhibited the growth of pathogen indicator organisms, showing their potential as antagonist strains, which should give these bacteria a competitive advantage during stone colonization: they are equipped to compete for space and resources against the other members of the community, as recently showed during the colonization of “mini-oases” plant-mediated in hyperarid desert ecosystems ( Marasco et al, 2022 ). Also, these microorganisms should not be ignored for their potential in the research for natural products with biotechnological applications.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Driven by the substantial overlap in the structures of newly discovered antimicrobial compounds from Streptomyces , researchers have begun to focus on rare actinobacteria, which are viewed as vast potential reservoirs of novel natural products ( Dhakal et al, 2017 ). Some of the rare actinobacteria detected in this study, such as members of Actinokineospora , Micromonospora , and Nocardia , inhibited the growth of pathogen indicator organisms, showing their potential as antagonist strains, which should give these bacteria a competitive advantage during stone colonization: they are equipped to compete for space and resources against the other members of the community, as recently showed during the colonization of “mini-oases” plant-mediated in hyperarid desert ecosystems ( Marasco et al, 2022 ). Also, these microorganisms should not be ignored for their potential in the research for natural products with biotechnological applications.…”
Section: Discussionsupporting
confidence: 67%
“…Data related to climate (max and min temperature and precipitation) were collected from climate knowledgeportal.worldbank.org, considering the period 1991-2020. Aridity values were obtained from the package R Envirem (Title and Bemmels, 2018) at the resolution of 1 km 2 and mapped as described in (Marasco et al, 2022). At each location, three areas of 1 m × 1 m were sampled, and further used as replicates.…”
Section: Sampling Sites Stones Collection and Preparationmentioning
confidence: 99%
“…These results are in line with a recent study by Hanusch and colleagues ( 40 ) suggesting that more deterministic processes such as niche filtering and biotic interactions are the main drivers of community assembly over the course of succession. A recent study conducted in a hyperarid environment also suggested that plants may have coevolved with specific bacterial taxa that possess the capacity to improve the fitness and survival of the host plant ( 41 ). Our study suggests a strong host-driven selection for specific functional traits of the plant-associated microbial community over the course of the revegetation event.…”
Section: Discussionmentioning
confidence: 99%
“…These microbial hotspots are particularly enriched in microbial cells when developed in extreme environments, such as harsh terrestrial ecosystems (deserts and drylands) and oligotrophic waters (Red Sea and brine pools). For example, the plant rhizosphere – the soil region directly influenced by plant roots – contains 3–4 orders of magnitude higher population density than surrounding bulk soils (Lv et al., 2023 ), which is exacerbated in deserts where nutrients (notably soil C, N and P) are limited (Marasco et al., 2022 ). While the rhizosphere microbiome is generally studied as a functionality and ecosystem service delivery hotbed, this microbial hotspot concomitantly hosts heightened intense competition between colocalized microorganisms for nutrients and space (Marasco et al., 2022 ).…”
Section: Where (Can) We Find Novel Antibiotics?mentioning
confidence: 99%